The Impact of Colon Cancer Sites on Survival Rates after Curative Resection and Adjuvant Chemotherapy: A SingleCenter Study - Jaruhathai, Sureerat; Santidamrongkul, Athit; Wiwitkeyoonwong, Jirapath; Duangnapa, Benjawongsathien (Asian Pacific Journal of Cancer Care, 2022)
Background: Most recent studies indicate that right-sided colon cancer is associated with a significantly higher mortality rate. Multivariate analyses showed that the patient’s age, sex, mode of presentation, co-morbidity, and the stage had significantly influenced their survival. Although the primary tumor location has an impact on the overall survival in metastatic settings, the laterality of early-stage colon cancer might also affect the disease-free survival and determine the duration of adjuvant chemotherapy for each side. This study aimed to compare overall survival and disease-free survival between left-sided and right-sided high-risk stage II and stage III colon cancer in patients from a single institute. Methods: This retrospective cohort study was conducted between January 2004 and December 2017. Data on 153 patients who underwent curative resection and adjuvant chemotherapy for colon cancer were retrieved from an existing database. Results: We found that the five-year disease-free survival rates were 63.20% for left-sided colon cancer and 51.11% for right-sided colon cancer (P-value < 0.05). The five-year overall survival rates were 66.98% for left-sided colon cancer and 57.77% for right-sided colon cancer (P-value 0.063). The right-sided primary tumor location was associated with a significantly higher mortality rate (HR: 2.28; 95%CI 1.38–5.8; P-value: 0.004). Conclusion: The results of this study confirmed that patients with high-risk stage II and stage III colon cancer who had right-sided tumors were significantly more likely to have decreased disease-free survival and overall survival. Further prospective studies should focus on tumor genetics and proper durations of adjuvant chemotherapy to maximize the benefit of treatment with acceptable toxicity.